TANGGUNGJAWAB HUKUM PERDATA DOKTER GIGI DALAM MENJALANKAN PRAKTIK AKIBAT PERBUATAN MELAWAN HUKUM - Qotrunnada, Zumar Salma; Saputra, Rizki Adi; Nugroho, Fajar Tri; Yuni Lestari, Ahdiana (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
The dentist profession is a profession that carries great risks. The reason is, a dentist has the responsibility to carry out medical procedures on his patients properly with the aim of curing or providing medical assistance to the patient. However, quite a few dentists commit negligence or medical malpractice which can cause harm to their patients. Therefore, dentists must be legally responsible for their actions, whether from civil law, criminal law, or other regulations relating to the profession of dentists. This article examines the legal consequences and responsibilities of dentists if medical malpractice occurs. This writing uses a type of juridical research sourced from secondary data which includes primary and secondary legal materials.